(untitled) (Baghdad Science Journal, 2006)
in the present investigation new eight poly esrers as schiff bases wich containing pendant imine group were synthesized by treatment of poly acryloyl chlodire with ethanol amine group were synthesized by treatment of poly acryloyl chloride with ethanol